Psychological Reactions among Staffs of a Tertiary Eye Hospital in Eastern Nepal during COVID-19 Pandemic - Gautam Joshi, Rinku; Joshi, Purushottam; Shrestha, Pranav; Basnet, Prabha Subedi; Mahat, Pawan (Nepalese Journal of Ophthalmology, 2021)
Introduction: Eye examination and different procedures performed in close contact with eye and face, put medical and non medical staff of an eye hospital at higher risk for COVID-19. This causes increased psychological burden. The objective of this study was to find out depression, anxiety, stress and insomnia among Mechi Eye Hospital staff. Materials and methods: A web based cross-sectional study among Mechi Eye Hospital staff was done from 1st to 20th July 2020. Insomnia Severity Scale and DASS-21 were used. Results: Out of 220, 190 (86.6%) participated, 63.2% were female and 61.05% were medical staff with an overall mean age of 31.1±8.4 years. Overall prevalence of anxiety, depression, insomnia and stress were 20.5%, 18.9%, 16.3% and 12.6% respectively and those were common in female with 63.9% (p value <0.02), 64.1% (p value 0.5), 58.4% (p value 0.2) and 100% (p value <0.01) respectively. Depression, anxiety and insomnia were common in the age group 30-39 years (50%, p value< 0.02), 20-29 years (56.4%, p value 0.1) and 20-29 years (70.9%, p value 0.8) respectively. Stress was common in 20-29 years and 30-39 years, 45.8% each (p value <0.03). Depression (75%, p value 0.2), anxiety (71.7%, p value 0.9) and stress (70.8%, p value 1.0) were common in medical staff. Insomnia was present in medical staff only (p value<0.01). Conclusion: Mechi Eye Hospital staff had greater prevalence of psychological reaction than the national baseline during the pandemic which was more common in female, younger age and medical staff.